Growth differentiation factor 15 is a myomitokine governing systemic energy homeostasis - Chung, Hyo Kyun (J Cell Biol, 2017)
Reduced mitochondrial electron transport chain activity promotes longevity and improves energy homeostasis via cell-autonomous and –non-autonomous factors in multiple model systems. This mitohormetic effect is thought to involve the mitochondrial unfolded protein response (UPR(mt)), an adaptive stress-response pathway activated by mitochondrial proteotoxic stress. Using mice with skeletal muscle–specific deficiency of Crif1 (muscle-specific knockout [MKO]), an integral protein of the large mitoribosomal subunit (39S), we identified growth differentiation factor 15 (GDF15) as a UPR(mt)-associated cell–non-autonomous myomitokine that regulates systemic energy homeostasis. MKO mice were protected against obesity and sensitized to insulin, an effect associated with elevated GDF15 secretion after UPR(mt) activation. In ob/ob mice, administration of recombinant GDF15 decreased body weight and improved insulin sensitivity, which was attributed to elevated oxidative metabolism and lipid mobilization in the liver, muscle, and adipose tissue. Thus, GDF15 is a potent mitohormetic signal that safeguards against the onset of obesity and insulin resistance.